Transglycosylation specificity of Acremonium sp. α-rhamnosyl-β-glucosidase and its application to the synthesis of the new fluorogenic substrate 4-methylumbelliferyl-rutinoside - Mazzaferro, Laura (2012)
Transglycosylation potential of the fungal diglycosidase α-rhamnosyl-β-glucosidase was explored. The biocatalyst was shown to have broad acceptor specificity toward aliphatic and aromatic alcohols. This feature allowed the synthesis of the diglycoconjugated fluorogenic substrate 4-methylumbelliferyl-rutinoside. The synthesis was performed in one step from the corresponding aglycone, 4-methylumbelliferone, and hesperidin as rutinose donor. 4-Methylumbelliferyl-rutinoside was produced in an agitated reactor using the immobilized biocatalyst with a 16% yield regarding the sugar acceptor. The compound was purified by solvent extraction and silica gel chromatography. MALDI-TOF/TOF data recorded for the [M+Na]+ ions correlated with the theoretical monoisotopic mass (calcd [M+Na]+: 507.44 m/z; obs. [M+Na]+: 507.465 m/z). 4-Methylumbelliferyl-rutinoside differs from 4-methylumbelliferyl-glucoside in the rhamnosyl substitution at the C-6 of glucose, and this property brings about the possibility to explore in nature the occurrence of endo-β-glucosidases by zymographic analysis.